Graphs, dioids and semirings : new models and algorithms - Gondran, Michel (Springer, 2017)
The origins of Graph Theory date back to Euler (1736) with the solution of the celebrated 'Koenigsberg Bridges Problem'; and to Hamilton with the famous 'Trip around the World' game (1859), stating for the first time a problem which, in its most recent version a" the 'Traveling Salesman Problem' -, is still the subject of active research. Yet, it has been during the last fifty years or soa "with the rise of the electronic computersa "that Graph theory has become an indispensable discipline in terms of the number and importance of its applications across the Applied Sciences. Gra